Evaluación de la calidad del servicio al cliente, mediante la metodología servperf en el restaurante Dayanita de la ciudad de salcedo. - Espín Balseca, Teresa Anabel (2019)
The objective of this research work was to evaluate the perception of the customer quality service, using Servperf methodology, to it add value to Dayanita Restaurant at city Salcedo, which has been operating for approximately 11 years in the sector, The investigation was carried out with the purpose to know the perceptions and the service that clients receive since the disagreement at provided service is noted and it should be taken into account that the client must receive, a service of quality and warmth. A bibliographic and documentary investigation of several authors was carried out to gather information, based on the study carried out by the authors Cronin and Taylor, which consists of a perceptions set or questions categorized intangible elements, reliability, responsiveness, security, and empathy; They help to identify the inconveniences that have been committed by the staff working at Dayanita Restaurant on service quality terms. The methodology used was of an exploratory type to meet the needs and descriptive in a way that allowed to detail the data and characteristics of the population, additionally through a field investigation allowed to collect information through customer surveys and at the same time with a quantitative approach, which allowed to work in statistical form. By applying the Servperf model with the collected data, the weaknesses of each dimensions were evidenced, where improvements must be made to achieve greater customer satisfaction through the quality of provided service.